Depression, suicidal ideation and the COVID-19 pandemic in Europe - a systematic review - Ana Rita da Silva Costa (2021)
Introduction: The 2019 coronavirus disease pandemic has led to an unprecedented situation with a significant impact on mental health. This systematic review aims to analyse the existing literature that reports the effect of the pandemic on depression and suicidal ideation in Europe among general public and to identify groups at increased risk. Methods: A search was conducted on 2 databases, PubMed and Scopus, for records published until January of 2021. Studies were selected based on predetermined inclusion and exclusion criteria. The quality of the included studies was assessed by the Newcastle-Ottawa Scale, adapted for cross-sectional studies. Results: From a total of 335 articles found, 35 were included in this review. The prevalence of depressive symptoms ranged from 8,3% to 64% and the prevalence of suicidal thoughts, from 4,5% to 18% in the general population of several European countries. Some of the risk factors associated with our primary outcome were: female gender, younger age, student status, pre-existing physical/psychiatric diseases, non-adaptative coping strategies, isolation and low socioeconomic status. Discussion: The rate of depressive symptoms and suicidal ideation in the records we reviewed was superior to pre-pandemic established numbers, showing a possible negative effect of the pandemic on mental health. Conclusion: COVID-19's consequences go beyond the physical damage, as they also have a significant impact on general public's mental health. Therefore, it is urgent to develop psychological interventions to preserve the mental health of individuals and face this as an international public health priority.